Composite material repairing slurry and preparation process thereof
Through the composite repair of components A and B, the problems of low bond strength and poor high temperature resistance of composite repair materials are solved, and efficient repair of carbon fiber composite materials is achieved, simplified the operation process and improved heat resistance sex.
Patent Information
- Application Number
- CN202411731165.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing composite repair materials have low bond strength, poor high temperature resistance, and cumbersome repair processes, making it difficult to meet the repair needs of carbon fiber composites in high temperature environments.
Composite materials of A and B are used to repair the slurry, which includes hydroxyacrylate monomer, polyethylene glycol monomethyl ether, polyisocyanate, acrylate monomer, blocking agent and initiator, and B Including epoxy resins, reinforced fibers, nanoparticles, ethyl acetate and phosphoric acid, the bond strength and heat resistance are improved by specific mixing and heating treatment.
It significantly improves the bonding strength and heat resistance of composite repair slurries, simplifies the repair process, and is suitable for carbon fiber composite repair in high temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a composite material repair slurry and a preparation process thereof. Background Art
[0002] Carbon fiber reinforced resin-based composites are widely used in the fields of aviation, aerospace, spacecraft and missiles. Carbon fiber composites have a large modulus, low density, high specific strength and specific stiffness, and have unique advantages that metals cannot match. The specific strength and specific stiffness of carbon fiber composites modified with epoxy resin are significantly better than those of aluminum alloys. However, carbon fiber composites may suffer varying degrees of damage during the production process due to design changes or when parts are subjected to low-speed impact. Carbon fiber composite panels have fiber breakage, matrix fragmentation and interlayer delamination, and the core material of the carbon fiber composite will have honeycomb crushing or foam fragmentation, and debonding from the panel. Once the carbon fiber composite parts are severely damaged, failure to repair them in time will not only affect work efficiency, but may also pose a safety hazard.
[0003] Patent US4358480 discloses a method for repairing surface damage of a porous refractory substrate, which includes first hydrolyzing ethyl orthosilicate, and then curing the hydrolyzed ethyl orthosilicate under heating conditions, so as to use it as an inorganic adhesive. However, the ethyl orthosilicate adhesive of the repair material of this method is very easy to pulverize at high temperatures, resulting in failure of the repair material. Patent CN112848417A discloses a method for repairing cracks in a carbon fiber composite material product of a hydrogen fuel cell vehicle, which uses a combination of carbon fiber cloth and A / B two-component epoxy resin to repair the crack area of the carbon fiber composite material product. However, this technology has the disadvantages of cumbersome repair process operation steps and inconvenient repair, and most A / B two-component epoxy resins have a temperature resistance of about 100°C, and only some can reach about 280°C, and the high temperature resistance is poor. Summary of the invention
[0004] In view of the technical problems that existing composite material repair materials have low bonding strength, poor high temperature resistance and complicated repair process operation, the present invention provides a composite material repair slurry and a preparation process thereof.
[0005] In a first aspect, the present invention provides a composite material repair slurry, comprising a component A and a component B. In parts by weight, component A includes: 5 to 15 parts of hydroxy acrylate monomer, 50 to 60 parts of polyethylene glycol monomethyl ether, 50 to 60 parts of polyisocyanate, 20 to 40 parts of acrylate monomer, 10 to 60 parts of blocking agent, and 3 to 10 parts of initiator; Component B includes: 30-40 parts of epoxy resin, 10-20 parts of reinforcing fiber, 4-10 parts of nanoparticles, 4-10 parts of ethyl acetate, and 2-5 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 1-4:1.
[0006] Furthermore, the polyisocyanate is one or a mixture of two or more of toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate.
[0007] Furthermore, the blocking agent is one or a mixture of two or more of 3,5-dimethylpyrazole, acetone oxime, ethanol, diethyl malonate, and phenol.
[0008] Furthermore, the initiator is one or more of potassium persulfate, ammonium persulfate, potassium persulfate-sodium bisulfite or ammonium persulfate-sodium bisulfite.
[0009] Furthermore, the nanoparticles are selected from one of nano-titanium dioxide, nano-aluminum oxide and carbon nanotubes.
[0010] In a second aspect, the present invention further provides a process for preparing the composite material repair slurry, comprising the following steps: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and polyisocyanate, stir evenly, fill with nitrogen for protection, react at 60-120°C for 1-5 hours; add blocking agent, react at 50-70°C for 1-2 hours; add acrylate monomer, high-speed shear at 1000-2000 rpm for 30-120 minutes, and then homogenize for 30-120 minutes; add initiator, react at 60-90°C for 3-9 hours to obtain component A; (2) Preparation of component B: Infiltrate the nanoparticles and reinforcing fibers with half the mass of ethyl acetate for 48-56 hours and set aside; dissolve the epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50°C for more than 10 minutes; add the infiltrated nanoparticles and reinforcing fibers, and stir at 300-1500 rpm for 25-30 minutes to obtain component B; (3) Component A and component B are mixed, and stirred while heating to obtain a composite material repair slurry.
[0011] Furthermore, in step (1), the temperature of high-speed shearing and homogenization is maintained at 30-100°C.
[0012] Furthermore, in step (2), after adding the impregnated nanoparticles and reinforcing fibers, the mixture is stirred at a low speed of 300-500 rpm for 15-20 min, and at a high speed of 1000-1500 rpm for 5-10 min.
[0013] Furthermore, in step (3), the heating temperature is 50-80° C. and the stirring speed is 1000-1200 rpm.
[0014] The beneficial effects of the present invention are: The composite material repair slurry provided by the present invention uses acrylate monomer to modify isocyanate, thereby improving the cross-linking effect of isocyanate emulsion as a curing agent; ethyl acetate, epoxy resin, and phosphoric acid are used to react to open the epoxy ring and react with isocyanate, thereby further improving the curing and cross-linking degree of epoxy resin and isocyanate, and greatly improving the bonding strength and heat resistance of the composite material repair slurry. In addition, the addition of nanoparticles can improve the efficiency of curing and cross-linking; the reinforcing fibers use carbon fibers and asbestos fibers, so that the strength and heat resistance of the repair slurry after curing are improved at the same time. DETAILED DESCRIPTION
[0015] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0016] Example 1 A composite material repair slurry, comprising component A and component B, In parts by weight, component A includes: 15 parts of hydroxy acrylate monomer, 50 parts of polyethylene glycol monomethyl ether, 50 parts of toluene diisocyanate, 20 parts of acrylate monomer, 40 parts of 3,5-dimethylpyrazole, and 3 parts of potassium persulfate; Component B includes: 30 parts of epoxy resin, 10 parts of reinforcing fiber, 4 parts of nano titanium dioxide, 4 parts of ethyl acetate, and 2 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of the carbon fiber to the asbestos fiber is 1:1.
[0017] The preparation process is as follows: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and toluene diisocyanate, stir evenly, fill with nitrogen for protection, and react at 60-120°C for 1 hour; add 3,5-dimethylpyrazole, and react at 50-70°C for 1 hour; add acrylate monomer, high-speed shear at 1000 rpm for 120 minutes, and then homogenize for 30 minutes, with the high-speed shear and homogenization temperatures maintained at 30-100°C; add potassium persulfate, and react at 60-90°C for 3 hours to obtain component A; (2) Preparation of component B: Use half the mass of ethyl acetate to soak nano-titanium dioxide and reinforcing fibers for 48 hours and set aside; dissolve epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50 °C for 10 minutes; add the soaked nano-titanium dioxide and reinforcing fibers, stir at a low speed of 300 rpm for 20 minutes, and stir at a high speed of 1000 rpm for 10 minutes to obtain component B; (3) Component A and component B are mixed, and heated while stirring at a heating temperature of 50 to 80°C and a stirring speed of 1000 rpm to obtain a composite material repair slurry.
[0018] Comparative Example 1 The difference from Example 1 is that no acrylate monomer is added in step (1), and the other treatments are the same.
[0019] Example 2 A composite material repair slurry, comprising component A and component B, In parts by weight, component A includes: 5 parts of hydroxy acrylate monomer, 50 parts of polyethylene glycol monomethyl ether, 20 parts of diphenylmethane diisocyanate, 30 parts of hexamethylene diisocyanate, 20 parts of acrylate monomer, 10 parts of acetone oxime, and 3 parts of ammonium persulfate; Component B includes: 30 parts of epoxy resin, 10 parts of reinforcing fiber, 4 parts of carbon nanotubes, 4 parts of ethyl acetate, and 2 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 2:1.
[0020] The preparation process is as follows: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether, diphenylmethane diisocyanate and hexamethylene diisocyanate, stir evenly, fill with nitrogen for protection, and react at 60-120°C for 1 hour; add acetone oxime, and react at 50-70°C for 2 hours; add acrylate monomer, high-speed shear at 1200 rpm for 60 minutes, and then homogenize for 60 minutes, with the high-speed shear and homogenization temperatures maintained at 30-100°C; add ammonium persulfate, and react at 60-90°C for 6 hours to obtain component A; (2) Preparation of component B: soak carbon nanotubes and reinforcing fibers with half the mass of ethyl acetate for 50 h and set aside; dissolve epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50 °C for 11 min; add the soaked carbon nanotubes and reinforcing fibers, stir at a low speed of 400 rpm for 18 min and at a high speed of 1200 rpm for 8 min to obtain component B; (3) Component A and component B are mixed, and stirred while heating at a temperature of 50 to 80°C and a stirring speed of 1200 rpm to obtain a composite material repair slurry.
[0021] Comparative Example 2 The difference from Example 2 is that ethyl acetate and phosphoric acid are not used in step (2), and the epoxy resin is directly mixed with the carbon nanotubes and the reinforcing fibers. The other processes are the same.
[0022] Example 3 A composite material repair slurry, comprising component A and component B, In parts by weight, component A includes: 10 parts of hydroxy acrylate monomer, 55 parts of polyethylene glycol monomethyl ether, 55 parts of diphenylmethane diisocyanate, 30 parts of acrylate monomer, 35 parts of ethanol, and 6 parts of potassium persulfate-sodium bisulfite; Component B includes: 35 parts of epoxy resin, 15 parts of reinforcing fiber, 7 parts of nano-alumina, 7 parts of ethyl acetate, and 3 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 3:1.
[0023] The preparation process is as follows: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and diphenylmethane diisocyanate, stir evenly, and protect with nitrogen. React at 60-120°C for 3 hours; add ethanol and react at 50-70°C for 1.5 hours; add acrylate monomer, high-speed shear at 1500 rpm for 30 minutes, and then homogenize for 80 minutes, with the high-speed shear and homogenization temperatures maintained at 30-100°C; add potassium persulfate-sodium bisulfite and react at 60-90°C for 6 hours to obtain component A; (2) Preparation of component B: Use half the mass of ethyl acetate to soak the nano-alumina and reinforcing fibers for 48-56 hours and set aside; dissolve the epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50°C for more than 10 minutes; add the soaked nano-alumina and reinforcing fibers, stir at a low speed of 400 rpm for 18 minutes, and at a high speed of 1200 rpm for 8 minutes to obtain component B; (3) Component A and component B are mixed, and stirred while heating at a temperature of 50 to 80°C and a stirring speed of 1100 rpm to obtain a composite material repair slurry.
[0024] Comparative Example 3 The difference from Example 3 is that no nano-alumina is added, and other treatments are the same.
[0025] Example 4 A composite material repair slurry, comprising component A and component B, In parts by weight, component A includes: 10 parts of hydroxy acrylate monomer, 55 parts of polyethylene glycol monomethyl ether, 55 parts of hexamethylene diisocyanate, 30 parts of acrylate monomer, 35 parts of diethyl malonate, and 7 parts of ammonium persulfate-sodium bisulfite; Component B includes: 35 parts of epoxy resin, 15 parts of reinforcing fiber, 8 parts of nano-alumina, 5 parts of ethyl acetate, and 4 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 4:1.
[0026] The preparation process is as follows: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and hexamethylene diisocyanate, stir evenly, and protect with nitrogen. React at 60-120°C for 4 hours; add diethyl malonate and react at 50-70°C for 2 hours; add acrylate monomer, high-speed shear at 3000-10000 rpm for 80 minutes, and then homogenize for 80 minutes, with the high-speed shear and homogenization temperatures maintained at 30-100°C; add ammonium persulfate-sodium bisulfite and react at 60-90°C for 5 hours to obtain component A; (2) Preparation of component B: Infiltrate nano-alumina and reinforcing fibers with half the mass of ethyl acetate for 50 hours and set aside; dissolve epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50°C for 10 minutes; add the infiltrated nano-alumina and reinforcing fibers, stir at a low speed of 500 rpm for 15 minutes, and stir at a high speed of 1200 rpm for 10 minutes to obtain component B; (3) Component A and component B are mixed, and stirred while heating at a temperature of 50 to 80°C and a stirring speed of 1200 rpm to obtain a composite material repair slurry.
[0027] Comparative Example 4 The difference from Example 4 is that no reinforcing fiber is added.
[0028] Example 5 A composite material repair slurry, comprising component A and component B, In parts by weight, component A includes: 15 parts of hydroxy acrylate monomer, 60 parts of polyethylene glycol monomethyl ether, 30 parts of toluene diisocyanate, 30 parts of diphenylmethane diisocyanate, 40 parts of acrylate monomer, 60 parts of phenol, and 10 parts of ammonium persulfate-sodium bisulfite; Component B includes: 40 parts of epoxy resin, 20 parts of reinforcing fiber, 10 parts of carbon nanotubes, 10 parts of ethyl acetate, and 5 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 2:1.
[0029] The preparation process is as follows: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and polyisocyanate, stir evenly, fill with nitrogen for protection, and react at 60-120°C for 3 hours; add toluene diisocyanate and diphenylmethane diisocyanate, and react at 50-70°C for 1 hour; add acrylate monomer, high-speed shear at 1200 rpm for 60 minutes, and then homogenize for 60 minutes, and the high-speed shear and homogenization temperatures are maintained at 30-100°C; add ammonium persulfate-sodium bisulfite, and react at 60-90°C for 3 hours to obtain component A; (2) Preparation of component B: soak carbon nanotubes and reinforcing fibers with half the mass of ethyl acetate for 56 hours and set aside; dissolve epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50°C for 10 minutes; add the soaked carbon nanotubes and reinforcing fibers, stir at a low speed of 300 rpm for 20 minutes, and stir at a high speed of 1000 rpm for 10 minutes to obtain component B; (3) Component A and component B are mixed, and heated while stirring at a heating temperature of 50 to 80°C and a stirring speed of 1000 rpm to obtain a composite material repair slurry.
[0030] Comparative Example 5 The difference from Example 5 is that the weight ratio of carbon fiber to asbestos fiber is 5:1, and other treatments are the same.
[0031] Example 6 A composite material repair slurry, comprising component A and component B, In parts by weight, component A includes: 15 parts of hydroxy acrylate monomer, 60 parts of polyethylene glycol monomethyl ether, 30 parts of toluene diisocyanate, 30 parts of hexamethylene diisocyanate, 40 parts of acrylate monomer, 60 parts of diethyl malonate, 5 parts of ammonium persulfate and 5 parts of potassium persulfate-sodium bisulfite; Component B includes 40 parts of epoxy resin, 20 parts of reinforcing fiber, 10 parts of carbon nanotubes, 10 parts of ethyl acetate, and 5 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 3:1.
[0032] The preparation process is as follows: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and polyisocyanate, stir evenly, and perform nitrogen protection, and react at 60-120°C for 5 hours; add a blocking agent, and react at 50-70°C for 2 hours; add acrylate monomer, perform high-speed shearing at 1500 rpm for 60 minutes, and then homogenize for 120 minutes, with the high-speed shearing and homogenizing temperatures maintained at 30-100°C; add an initiator, and react at 60-90°C for 9 hours to obtain component A; (2) Preparation of component B: soak carbon nanotubes and reinforcing fibers with half the mass of ethyl acetate for 56 hours and set aside; dissolve epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50°C for 10 minutes; add the soaked carbon nanotubes and reinforcing fibers, stir at a low speed of 500 rpm for 20 minutes, and stir at a high speed of 1500 rpm for 10 minutes to obtain component B; (3) Component A and component B are mixed, and stirred while heating at a temperature of 50 to 80°C and a stirring speed of 1200 rpm to obtain a composite material repair slurry.
[0033] Example 7 Repair of carbon fiber composite material The performance of the composite material repair slurry prepared in Examples 1-6 was tested. The composite material repair slurry was coated on the carbon fiber composite material to be repaired, heat cured at 120°C for 24 hours, and then heat resistance and strength tests were performed, wherein the strength test included the tensile strength and bending strength of the repaired part of the carbon fiber composite material, and the results are shown in Table 1. The above-mentioned carbon fiber composite material to be repaired is a material after the commercially available carbon fiber composite material is broken by shear force. The commercially available carbon fiber composite material was purchased from Xinyu Chulu Trading Co., Ltd., and the product model is Guka Beast Frame. The heat resistance is determined by the method shown in Part 2: Plastics and Hard Rubber of "GB / T 1634.2-2019 Determination of Deformation Temperature of Plastics under Load"; the tensile strength test method is determined by the method shown in "GB / T 1040.1-2006 Determination of Tensile Properties of Plastics".
[0034] Table 1 Test results of composite material repair slurry performance
[0035] Although the present invention has been described in detail by way of preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and such modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily conceive of changes or substitutions within the technical scope disclosed by the present invention, and such changes or substitutions shall be within the scope of protection of the present invention.
Claims
1. A composite material repair slurry, characterized in that: It includes component A and component B. In parts by weight, component A includes: 5 to 15 parts of hydroxy acrylate monomer, 50 to 60 parts of polyethylene glycol monomethyl ether, 50 to 60 parts of polyisocyanate, 20 to 40 parts of acrylate monomer, 10 to 60 parts of blocking agent, and 3 to 10 parts of initiator; Component B includes: 30-40 parts of epoxy resin, 10-20 parts of reinforcing fiber, 4-10 parts of nanoparticles, 4-10 parts of ethyl acetate, and 2-5 parts of phosphoric acid; the reinforcing fiber includes carbon fiber and asbestos fiber, and the weight ratio of carbon fiber to asbestos fiber is 1-4:
1.
2. The composite material repair slurry according to claim 1, characterized in that: The polyisocyanate is one or a mixture of two or more of toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate.
3. The composite material repair slurry according to claim 1, characterized in that: The blocking agent is one of 3,5-dimethylpyrazole, acetone oxime, ethanol, diethyl malonate and phenol, or a mixture of two or more thereof.
4. The composite material repair slurry according to claim 1, characterized in that: The initiator is one or more of potassium persulfate, ammonium persulfate, potassium persulfate-sodium bisulfite or ammonium persulfate-sodium bisulfite.
5. The composite material repair slurry according to claim 1, characterized in that: The nanoparticles are selected from one of nano-titanium dioxide, nano-aluminum oxide and carbon nanotubes.
6. A process for preparing the composite material repair slurry as claimed in claim 1, characterized in that: The following steps are involved: (1) Preparation of component A: Mix hydroxy acrylate monomer, polyethylene glycol monomethyl ether and polyisocyanate, stir evenly, fill with nitrogen for protection, react at 60-120°C for 1-5 hours; add blocking agent, react at 50-70°C for 1-2 hours; add acrylate monomer, high-speed shear at 1000-2000 rpm for 30-120 minutes, and then homogenize for 30-120 minutes; add initiator, react at 60-90°C for 3-9 hours to obtain component A; (2) Preparation of component B: Infiltrate the nanoparticles and reinforcing fibers with half the mass of ethyl acetate for 48-56 hours and set aside; Dissolve the epoxy resin in the other half of the mass of ethyl acetate, add phosphoric acid, and stir at 45-50°C for more than 10 minutes; add the infiltrated nanoparticles and reinforcing fibers, and stir at 300-1500 rpm for 25-30 minutes to obtain component B; (3) Component A and component B are mixed, and stirred while heating to obtain a composite material repair slurry.
7. The preparation process according to claim 6, characterized in that: In step (1), the temperature of high-speed shearing and homogenization is maintained at 30-100°C.
8. The preparation process according to claim 6, characterized in that: In step (2), after adding the impregnated nanoparticles and reinforcing fibers, stir at a low speed of 300-500 rpm for 15-20 min and at a high speed of 1000-1500 rpm for 5-10 min.
9. The preparation process according to claim 6, characterized in that: In step (3), the heating temperature is 50-80°C and the stirring speed is 1000-1200 rpm.
Citation Information
Patent Citations
Epoxy resin binder used for repairing blade and preparation method thereof
CN101698787A
Heat-resistant epoxy adhesive for non-excavation rehabilitation technology and preparation method of heat-resistant epoxy adhesive
CN104830262A
Acrylate modified blocked polyisocyanate emulsion and preparation method therefor
CN109851719A
Epoxy resin composition for coating
JP1994248050A
